Tinjauan Etika Kristen: Peran Guru Sebagai Penuntun dalam Pembentukan Karakter Siswa Generasi Milenial [A Review of Christian Ethics: The Role of Teachers in Guiding the Milenial Students' for Character Building] - Yulen Nikitha K. Ngundjurawa; Suriani Sukowati Arifin (Universitas Pelita Harapan, 2021)
The rise of cases that occur among millennials such as brawling and bullying signified how bad the character of the generation has turned out to be. The deterioration of human character is the fruit of sin, but Christ has redeemed believers that give hope for a renewal of one's character. This paper aims to examine the importance of the teacher's role as a guide in shaping the character of millennial generation students who are reviewed based on Christian ethical principles using literature review method. Character formation requires the principle of Christian ethics, which is the moral character of Jesus as the main standard of goodness and the character of Christ as a reference point in character formation so that it is the character of Christ that is integrated into the process of character formation. The conclusion of this paper is the teacher's role as a guide is very important in the formation of character. Teachers who are willing to direct their students as to have good character according to the character of Christ.